Modern portfolio management : moving beyond modern portfolio theory - Petzel, Todd E. (Hoboken, New Jersey : Wiley, 2022)
"Investment books typically focus on the deep academic literature from Modern Portfolio Theory (MPT) or are "how to" guides that attempt to paint investing as a much simpler process than it is. Successful textbooks that try to cover all the bases like the Wiley publications of Charles P. Jones and Frank K. Reilly are aimed at students who may become stock analysts, portfolio managers or corporate executives needing a comprehensive coverage of the basics. This book is written by an institutional investor for other investors. The topic is timely because the investment management industry is always evolving to incorporate new models and technology, while sometimes overlooking critical operational steps. The complete investor can evaluate the investment thesis behind any fund or product and incorporate it appropriately into a long-term portfolio. This book provides the tools necessary to do just that."--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Portfolio management